HPMA Copolymer-Conjugated Pirarubicin in Multimodal Treatment of a Patient with Stage IV Prostate Cancer and Extensive Lung and Bone Metastases - Dozono, Haruhiko; Yanazume, Shintaro; Nakamura, Hideaki; Etrych, Tomáš; Chytil, Petr; Ulbrich, Karel; Fang, Jun; Arimura, Takeshi; Douchi, Tsutomu; Kobayashi, Hiroaki; Ikoma, Michiaki; Maeda, Hiroshi (Targeted oncology, 2016)
Nanomedicine allows achievement of tumor-selective drug delivery because of the enhanced permeability and retention (EPR) effect of solid tumors. We report here the first clinical application of a new agent-HPMA copolymer-conjugated pirarubicin (P-THP)-with a molecular size of about 8 nm, or 38.5 kDa. A patient had advanced prostate cancer with multiple metastases in the lung, pelvis, femur, and perhaps the sacrum. In April 2013, this 60-year-old patient started treatment with leuprorelin and estradiol, which continued until July 2014, but the patient became refractory to this treatment. So the patient underwent proton beam radiotherapy targeted to the primary prostate cancer, and P-THP was administered for numerous metastatic tumor nodules concomitantly with radiotherapy. This combination therapy had remarkable results, with complete remission of multiple metastases in the lung and bone. The prostate-specific antigen (PSA) value was decreased from about 1000 ng/mL on April 30, 2013, to about 100 ng/mL on June 24, 2013, with hormone therapy, but rose again to 964.2 ng/mL and then to 1472 ng/mL in July 2013, during leuprorelin administration. P-THP treatment administered concomitantly with proton beam irradiation was started in August 2013. The PSA value was decreased to 102 ng/mL on August 26, 2013, and then to 0.971 ng/mL on October 8, 2013, and 0.277 ng/mL on January 15, 2015. The P-THP doses ranged from 30 to 75 mg of free THP equivalent/patient every 2-3 weeks without signs of serious toxicity, such as cardiovascular side effects or a reduction in quality of life. No evidence of relapse was found more than 20 months after P-THP administration. This case demonstrates the value of hydrazone-bonded polymeric drugs in multimodal therapy.
Keywords: Doxorubicin; methakryláty; Prognosis; Middle Aged; mužské pohlaví; nádory prostaty; Methacrylates; nádory plic; lékové transportní systémy; nádory kostí; Antineoplastic Agents; kombinovaná terapie; Neoplasm Staging; doxorubicin; prognóza; protinádorové látky; Prostatic Neoplasms; Humans; Bone Neoplasms; lidé středního věku; Combined Modality Therapy; staging nádorů; Drug Delivery Systems; Lung Neoplasms; lidé; Male